Energy Conservation in the Cooling and Contracting Upper Mesosphere and Lower Thermosphere - Martin G. Mlynczak; Linda A. Hunt; Rolando Garcia; Manuel Lopez‐Puertas; Christopher J. Mertens; Nabil Nowak; B. Thomas Marshall (Geophysical Research Letters)
Abstract Time series of radiative cooling of the upper mesosphere and lower thermosphere (UMLT) by carbon dioxide (CO2) are examined for evidence of trends over 20 years. Radiative cooling rates in K day−1 provided by the SABER instrument are converted to time series of infrared power radiated from three distinct layers between 0.1 hPa and 0.0001 hPa (65–105 km). Linear regression against time and a predictor for solar variability provides estimates of the trend in exiting longwave radiation (ELR) from these layers. Trends in ELR are not significantly different from zero at 95% or 99% confidence in each layer. These results demonstrate energy conservation in the UMLT on decadal time scales and show that the UMLT continues to radiate the same amount of energy it receives despite cooling and contracting over two decades. These results are enabled by the long‐term stability of the SABER instrument calibration.